IMPLEMENTASI MATA KULIAH KESEHATAN DAN GIZI DENGAN TEMA SISTEM KEKEBALAN TUBUH PADA ANAK USIA DINI - Sri Purwanti; Wury Damayantie; Norlaila Norlaila (Jurnal Abdimas Bina Bangsa, 2024)
The final report of the PKM group II Prodi PG-AUD University of Balikpapan is entitled "Implementation of the AUD School of Health and Nutrition with the theme of Immunity System in Early Childhood". The aim of this PKM is to provide direct experience to students in implementing material about the immune system in early childhood. The event will take place on May 16, 2024 at Ekadyasa, Balikpapan South. Involved in this activity are the guardians of students and educational staff of Ekadyasa School, lecturers and five students of Prodi PG-AUD University of Balikpapan. The activity began with a greeting, continued with a material presentation about the immune system of the child by the student. Then a question-and-answer session was held between the speaker and the attendant. The program is getting good results and satisfying. Students gain hands-on experience in implementing courses and interacting with the community